Ferritin in Crohn's disease tissue: detection by electron microscopy. - Whorwell, P J (1976)
Using immune electron microscopy, an attempt has been made to visualise viral particles in Crohn's disease tissue and faeces. No particles resembling viruses were observed, but in the absence of a specific antiserum a negative result does not exclude the presence of a virus, particularly if it is sparsely distributed. Compared with controls, an abundance of a 12 nm particle was found in all Crohn's disease tissue and one small intestinal lymphoma. This particle has been identified as ferritin and is unlikely to be of aetiological significance.